2021
DOI: 10.3389/fpsyg.2021.658402
|View full text |Cite
|
Sign up to set email alerts
|

Declarative Memory Predicts Phonological Processing Abilities in Adulthood

Abstract: Individual differences in phonological processing abilities have often been attributed to perceptual factors, rather than to factors relating to learning and memory. Here, we consider the contribution of individual differences in declarative and procedural memory to phonological processing performance in adulthood. We examined the phonological processing, declarative memory, and procedural memory abilities of 79 native English-speaking young adults with typical language and reading abilities. Declarative memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Thus, it is possible to argue these results have stemmed from the difficulties that children from the DLD group present in the encoding and storing of the phonological information of the new “words” rather than from difficulties in using explicit knowledge/explicit learning mechanisms to assist SL per se (see Alt and Plante, 2006 ; Lum et al, 2012 , 2015 ). This possibility should be considered, as children from the DLD group present, indeed, lower phonological working memory skills than children from the TLD group, as assessed by the nonword repetition task from the LSST (see Table 1 ), and these skills were proven to be strongly related to declarative memory functioning (e.g., Alt and Plante, 2006 ; Coady and Evans, 2008 ; Lum et al, 2012 , 2015 ; Arthur et al, 2021 ). To explore the role that this variable might have played in the results, we conducted yet another analysis based on the same factorial design reported in the Results section but taking the scores obtained in the nonword repetition task into account (i.e., as a covariable in the ANOVAs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible to argue these results have stemmed from the difficulties that children from the DLD group present in the encoding and storing of the phonological information of the new “words” rather than from difficulties in using explicit knowledge/explicit learning mechanisms to assist SL per se (see Alt and Plante, 2006 ; Lum et al, 2012 , 2015 ). This possibility should be considered, as children from the DLD group present, indeed, lower phonological working memory skills than children from the TLD group, as assessed by the nonword repetition task from the LSST (see Table 1 ), and these skills were proven to be strongly related to declarative memory functioning (e.g., Alt and Plante, 2006 ; Coady and Evans, 2008 ; Lum et al, 2012 , 2015 ; Arthur et al, 2021 ). To explore the role that this variable might have played in the results, we conducted yet another analysis based on the same factorial design reported in the Results section but taking the scores obtained in the nonword repetition task into account (i.e., as a covariable in the ANOVAs).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the compensatory role of DM in children with DLD is, however, contentious. While some studies found intact or even enhanced performance in DM tasks in children with DLD relative to TLD controls, particularly in studies using DM tasks involving nonverbal materials (e.g., Riccio et al, 2007 ; Lum et al, 2010 ; Lum and Conti-Ramsden, 2013 ; Lukács et al, 2017 ; Earle and Ullman, 2021 ; see, however, Bishop and Hsu, 2015 ; Kuppuraj et al, 2016 ; Lee, 2018 ), others reported DM impairments, especially those using DM tasks involving verbal materials (e.g., Lum et al, 2010 ; Lukács et al, 2017 ; McGregor et al, 2017 ; Haebig et al, 2019 ; see, however, Baird et al, 2010 ; Evans et al, 2022 ), even though differences tend to vanish when working memory measures were taken into account (e.g., Alt and Plante, 2006 ; Lum et al, 2012 , 2015 ; Arthur et al, 2021 ). Thus, it remains largely unknown whether children with DLD show or not deficits in the DM system and even if showing spared or enhanced DM performance, as some studies suggest, the extent to which these abilities can be effectively mobilized by DLD children to compensate for their PM deficits.…”
Section: Introductionmentioning
confidence: 99%